2022
DOI: 10.3390/w14111798
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Regulated Deficit Irrigation on Yield and Quality of Isatis indigotica in a Cold and Arid Environment

Abstract: Although regulated deficit irrigation may improve crop yields, little research has been conducted on the effects of water deficits on Isatis indigotica, a popular herbal medicine. Field experiments were conducted in 2016 and 2017 to study the effects of regulated deficit irrigation on the net photosynthetic rate, yield, water use efficiency (WUE), and quality of I. indigotica in northwest China. Plants at the vegetative and fleshy root growth stages were subjected to mild, moderate, and severe water deficits, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…By fitting the four models, it was found that the sensitivity index of the Minhas model was greater than one, which did not meet the model criterion of sensitivity index less than one [25]. The differences between the simulated and measured values fitted by the Blank model were far from each other, so it also did not meet its fitting criterion, which was different from the results of Wang Yucai [30] et al The reason for the different results may be the difference in the study crop, fertility division and experimental design, which led to the different final results. The Jensen and Stewart models had a better fit and the magnitude of the water deficit sensitivity index was in the following order: tuber bulking stage > tuber initiation stage > seedling stage > starch accumulation stage, which is consistent with the findings of Jiang, Jiang X [31], Shukla M K i [19], Kuu H [32] et al This indicates that during the period from tuber formation to tuber expansion, when the potato is in a critical period of excessive reproductive growth from nutritional growth, the crop needs sufficient water to supply the necessary water for growth, and therefore water stress is not appropriate at this stage, while during the seedling and starch accumulation stages the crop is purely nutritional or reproductive in nature and does not require much water, so moderate water stress can be applied.…”
Section: Discussionmentioning
confidence: 99%
“…By fitting the four models, it was found that the sensitivity index of the Minhas model was greater than one, which did not meet the model criterion of sensitivity index less than one [25]. The differences between the simulated and measured values fitted by the Blank model were far from each other, so it also did not meet its fitting criterion, which was different from the results of Wang Yucai [30] et al The reason for the different results may be the difference in the study crop, fertility division and experimental design, which led to the different final results. The Jensen and Stewart models had a better fit and the magnitude of the water deficit sensitivity index was in the following order: tuber bulking stage > tuber initiation stage > seedling stage > starch accumulation stage, which is consistent with the findings of Jiang, Jiang X [31], Shukla M K i [19], Kuu H [32] et al This indicates that during the period from tuber formation to tuber expansion, when the potato is in a critical period of excessive reproductive growth from nutritional growth, the crop needs sufficient water to supply the necessary water for growth, and therefore water stress is not appropriate at this stage, while during the seedling and starch accumulation stages the crop is purely nutritional or reproductive in nature and does not require much water, so moderate water stress can be applied.…”
Section: Discussionmentioning
confidence: 99%
“…The stem diameter was measured using vernier calipers at the upper, middle, and lower parts of the stem and then averaged. The leaf area index was weighed using the paper-cut weighing method [25,26]. After sampling and weighing the leaves of the plant, 1/50 of the leaves are taken and drawn on standard graph paper, and then the paper mold is cut out and weighed, and the leaf area index per plant is calculated as follows:…”
Section: Growth Indicatorsmentioning
confidence: 99%
“…In addition, drip irrigation, as one of the most effective watersaving irrigation technologies, is suitable for the irrigation of fruit trees, vegetables, cash crops, and greenhouses. Many studies have shown that drip irrigation can significantly increase tomato dry matter accumulation and yield compared with traditional irrigation methods, and when used in combination with soluble fertilizers, it can not only promote the uptake of tomato nutrients but also significantly improve fertilizer use efficiency [5,25]. At present, the cultivation of facility tomatoes under Moistube irrigation conditions and the rational application of soluble organic fertilizer in the Loess Plateau have not been explored in sufficient detail.…”
Section: Introductionmentioning
confidence: 99%
“…Both centralized and decentralized sewage treatment methods need to establish sewage treatment stations, and then rural domestic sewage is "concentrated" or "decentralized" according to the actual situation [7]. At this stage, the economic development of rural areas themselves has not yet met the needs of building sewage treatment points, and most rural areas rely on policy funds applied for by governments at or above the district and county levels at the township level.…”
Section: Sewage Treatment Facilitiesmentioning
confidence: 99%